2021
DOI: 10.1007/s13296-021-00489-8
|View full text |Cite
|
Sign up to set email alerts
|

Shear Capacity Analysis of Welded Steel I-Girders with Corrugated Webs based on First Yield

Abstract: Steel I beams or girders with sinusoidal corrugated profile webs have become popular in the recent development of the steel structural designs, since corrugated-web beams (CWBs) can provide better performance in terms of less deformation and more stability against buckling failure. It is verified in previous research that CWBs can be considered as an alternative to replace normal beams in the structural designs with their numerous favourable features. Since CWBs are being used as the main structural elements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Many researchers [15,24,49] have reported that there were many benefits in using the CWBs, including its material efficiency, better strengths, stronger stability, and less deformation mentioned, where these favourable features could attract more engineering designers specialising in various design regions. In this study, the highly consistent results in the comparisons indicate that the numerical methods by ASTM [37] and Sause et al [38] could appropriately estimate the maximum deflections in in SAP 2000.…”
Section: Effects Of Length Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers [15,24,49] have reported that there were many benefits in using the CWBs, including its material efficiency, better strengths, stronger stability, and less deformation mentioned, where these favourable features could attract more engineering designers specialising in various design regions. In this study, the highly consistent results in the comparisons indicate that the numerical methods by ASTM [37] and Sause et al [38] could appropriately estimate the maximum deflections in in SAP 2000.…”
Section: Effects Of Length Variationmentioning
confidence: 99%
“…Some researchers [4,7,15] have mentioned that the corrugated feature can improve the bending and shear strength of the CWBs with less deflection. To start with the load determination, firstly, the UDL w* is set to be the length, a is equal to a quarter of the corrugation length, I is the second moment of inertia about the major axis, α is the corrugation angle, b is the ratio of a and L, k b is the bending stiffness, and k s is the shear stiffness.…”
Section: Design and Analysis Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…As a new type of structure with two face sheets and a cell core, corrugated sandwich panels have often been used to replace traditional metal components to reduce weight. Corrugated sandwich panels offer many advantages, such as lightness, low construction cost, high specific strength, effective sound insulation, high energy absorption efficiency, and strong impact resistance [4][5][6][7][8][9]. Hence, corrugated steel sandwich panels are being used in ship construction, for example, in the Visby class corvettes built by the Swedish Navy [10], in the European research project SANDWICH [11], and in the smooth components of ships [12].…”
Section: Introductionmentioning
confidence: 99%